Eksistensi Masyarakat Islam dan Kristen terhadap Kegiatan Keagamaan dalam Perspektif Islam dan Kristen di Desa Jawi Jawi - Erika, Putri; Harahap, Indra; Nasution, Muhammad Ali Azmi (ANWARUL, 2023)
This research examines the Islamic and Christian Society's Animo towards Religious Activities in Jawi Jawi Village, Sei Kepayang Barat District, the Community in Jawi Jawi Village towards understanding religious teachings can be assessed as a stimulus that has an impact on a person's religious behavior. Religious behavior as an activity based on believed religious values, is influenced by the intensity of individual activity, the level of understanding of religious teachings, and the intensity in carrying out activities related to religious teachings. This research uses the type of research conducted by researchers is qualitative research with a theological approach. This research was conducted in Sei Jawi Jawi Village, Sei Kepayang District, Asahan District, North Sumatra Province. In this case researchers classify sources into two categories, namely primary sources and secondary sources and researchers collect data by means of observation, interviews and documentation. The results of this study are that religious activities are all forms of activities related to religious values, which are used as routines in daily life and used as guidelines in establishing relationships with Allah SWT and relationships with other human beings. The views of the Muslim and Christian communities on religious activities in Jawi Jawi Village are activities that are based on Islamic or Christian religious teachings which are a form of Islamic development and one of its goals is to help build morals, especially as a form of moral development in the Jawi Jawi Village community. With the activeness of a person in participating in religious activities, it is hoped that the quality of a person's faith will be better than before where this will appear in his moral behavior in everyday life. This means that Islamic and Christian religious activities contribute to the process of developing the morals of the people of Jawi Jawi Village.